COMMUNICATION STRATEGIES USED BY EFL STUDENTS IN IMPROVING SPEAKING SKILL - Rahmi Aulia Nurdini (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
This study aimed to investigate communication strategies (CSs) used by EFL students in improving speaking English. Methods employed were questionnaire, observation, and interview. Findings showed that students have improvement in speaking when they used communication strategies (CSs). The strategies used by the students such as non-linguistic means, appeal for help, and fillers or hesitation device, message abandonment, non-linguistic means, literal translation, code switching, appeal for help, and fillers or hesitation device. The study suggests that EFL practitioners pay attention to communication strategies (CSs) aspect to obtain the optimum results of teaching-learning processes.